The Application of the Project-Based Learning Model to the Learning of Poetry Writing Skills of Grade X Students of Vocational High School PGRI 2 Pasuruan - Salsabila, Salsabila; Suwadi, Suwadi; Sugianti, Sugianti (Pijar : Jurnal Penelitian Bidang Pendidikan dan Pembelajaran, 2025)
This study explores the application of the Project-Based Learning model to improve poetry writing skills among Grade X students at Vocational High School PGRI 2 Pasuruan within the framework of the Independent Curriculum. Although the curriculum promotes flexible and contextual learning, poetry instruction in vocational schools often remains conventional, leading to low student engagement and limited writing proficiency. This qualitative descriptive research involved classroom observations, interviews with Indonesian language teachers and students, and documentation of student poetry and learning materials. Data analysis followed Miles and Huberman’s interactive model, encompassing data reduction, display, and conclusion drawing. The results demonstrate that implementing the PjBL model enhances student motivation, critical thinking, collaboration, and creativity. Students actively participated in every phase of the project from idea development to poetry presentation, resulting in a more dynamic and meaningful learning experience. Teachers reported increased student engagement and autonomy, despite facing challenges such as diverse student abilities and time constraints. The study concludes that PjBL is an effective pedagogical model for fostering poetry writing skills in vocational education and aligns with the goals of the Independent Curriculum in promoting student-centered and experiential learning.